Pengaruh Volume Pembiayaan Bagi Hasil dan Pembiayaan Murabahah terhadap Kinerja Keuangan Bank Umum Syariah dengan NPF sebagai Variabel Moderasi - Mirasanti Wahyuni (Sekolah Tinggi Ilmu Ekonomi Bisnis dan Perbankan, 2016)
Islamic Banks have a high level of asset growth, but a growth rate of financing volume ineffective. Financing products are the determining factors of the asset and valuable resource, which can be used as a reference in the company's strategy to produce a good performance. The large volume of financing is estimated to have an influence on the performance of Islamic banks. This study was conducted to analyze the effect caused by the volume of financing when the NPF or their financing problems. The results of this study are NPF moderate the influence of financing volume-profit sharing based on the performance of Islamic banks are proxied by the ROA. The results of the second shows that the NPF has a significant influence in moderating influence on the performance of the volume of financing murabaha Islamic commercial bank.